Visual system and motor development in children: a systematic review. - Sánchez-González, María Carmen; Palomo‐Carrión, Rocío; De-Hita-Cantalejo, Concepción; Romero-Galisteo, Rita Pilar; Gutiérrez-Sánchez, Estanislao; Pinero‐Pinto, Elena (Wiley & Sons, 2022)
The aim of this study was to review the available scientific literature on the possible relationship between the visual system and motor development in children. Methods. This study was performed according to the Preferred Reporting Items for Systematic Reviews (PRISMA) statement recommendations. The review protocol is available in PROSPERO (CRD42021245341). Four different databases, namely Scopus, PubMed, CINAHL and Web of Science, were assessed from April 2005 to February 2021. To determine the quality of the articles, we used the Critical Appraisal Skills Programme (CASP) Quality Appraisal Scale, and a protocol was followed to define the levels of evidence on the basis of the Centre for Evidence-Based Medicine Levels of Evidence. The search strategy included terms describing motor development in children and adolescents with visual disorders. Results. Among the identified studies, 23 were included in the study. All selected articles examined the relationship between the visual system and development in children. The quality of most of the studies was moderate–high, and they were between evidence levels 2 and 4. Conclusions. Our systematic review revealed that all included studies established a relationship between the visual system and development in children. However, the methods for measuring the visual system and motor skills lacked uniformity.
Keywords: Ambliopía; Visión - Trastornos; Aprendizaje motor; Niños - Desarrollo; Amblyopia; Child development; Motor skills; Ocular motility disorders; Visual disorders